Maintaining Local Languages in the Elementary Schools in Indonesia through Pierre Bourdieu’s Cultural Reproduction Strategies - Mohammad Andi Hakim; Eri Kurniawan; Wawan Gunawan; Budi Hermawan (Al Ibtida: Jurnal Pendidikan Guru MI, 2024)
AbstractThis research examines cultural reproduction strategies for maintaining local languages in elementary schools in Indonesia. The academic struggle for local language maintenance programs needs to be refined with alternative thinking and solutions. The study was conducted using a qualitative approach and a library research and outlines various findings regarding local language maintenance programs in elementary schools. Maintaining local languages in the management of elementary schools in Indonesia can be done through Pierre Bourdieu’s cultural reproduction strategies through programs orientated towards strengthening aspects of 1) Habitus, which focuses on externalizing awareness of the importance of preserving local languages; 2) capital, which focuses on resources and supporting capacity for local language preservation; and 3) arena, which focuses on educational and learning activities. The design of strengthening local language preservation through habitus is carried out in several steps: 1) applying linguistic knowledge; 2) promoting language loyalty, pride, and awareness of norms; 3) engaging in literature on language preservation and authenticity; and 4) fostering a positive language attitude. Meanwhile, the capital strengthening program through resources and carrying capacity is carried out: 1) the implementation of the Indonesian Language Policy; 2) the promotion of family, neighborhood, and religious values; 3) linguistic diversity. The strengthening program implemented through the arena includes: 1) strategies that include formal learning, extracurricular activities, and mandatory activities; and 2) technology, documentation, and revitalization.Keywords: habitus, capital, arena, cultural reproduction.AbstrakPenelitian ini mengkaji strategi reproduksi budaya dalam pemertahanan bahasa daerah pada sekolah dasar di Indonesia. Perjuangan akademik terhadap program pemertahanan bahasa daerah perlu disempurnakan dengan pemikiran dan solusi alternatif. Penelitian ini dilakukan dengan pendekatan kualitatif dan telaah pustaka untuk menguraikan berbagai temuan mengenai program pemertahanan bahasa daerah di sekolah dasar. Pemertahanan bahasa daerah dalam pengelolaan sekolah dasar di Indonesia dapat dilakukan melalui strategi reproduksi budaya Pierre Bourdieu melalui program yang berorientasi pada penguatan aspek 1) habitus, yang fokus pada eksternalisasi kesadaran akan pentingnya pelestarian bahasa daerah; 2) kapital, yang fokus pada sumber daya dan daya dukung pelestarian bahasa daerah; dan 3) arena, yang fokus pada kegiatan pendidikan dan pembelajaran. Rancangan penguatan pelestarian bahasa daerah melalui habitus dilakukan dengan beberapa langkah: 1) penerapan pengetahuan linguistik; 2) mempromosikan kesetiaan berbahasa, kebanggaan, dan kesadaran terhadap norma; 3) menggeluti kepustakaan tentang pelestarian dan keaslian bahasa; dan 4) menumbuhkan sikap berbahasa yang positif. Sedangkan program penguatan kapital melalui sumber daya dan daya dukung dilakukan: 1) kebijakan Bahasa Indonesia; 2) keluarga, lingkungan sekitar, dan agama; 3) keberagaman bahasa. Program penguatan melalui arena tersebut adalah: 1) strategi meliputi pembelajaran formal, ekstrakurikuler, dan wajib; 2) teknologi, dokumentasi dan revitalisasi.Kata kunci: habitus, kapital, arena, reproduksi budaya.